Mustard seed oil meal as a protein supplement for fattening pigs on alfalfa pasture. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
Last year at the Livestock Feeders' Day, results of experiments were given on the use of mustard seed oil meal as a protein supplement for fattening pigs in the dry lot. The results showed that mustard seed oil meal was an excellent protein feed when mixed with tankage and other protein supplements and self fed free choice. Generally the gains were somewhat cheaper than where tankage alone was fed, but the gains were not quite so rapid. In the tests reported last year the mustard seed meal made up as much as 50 percent of the protein mixtures, in some of the lots. With mustard seed meal proving to be so satisfactory for dry lot feeding, it was thought desirable to obtain data on its efficiency in the pasture feeding of spring pigs.
Keywords: Swine; Mustard seed oil meal; Protein; Alfalfa pasture